Strengthening International Networks to Support Sustainable Development through Sharia Economics - Abrahan, Amnisuhailah binti; Zaini, Muhammad Zaki bin Haji; Muslimah, Yosi binnatul; Aprillia, Kinanti Dwi; Yunani, Zerli Feni; Zunaidi, Arif; Gunawan, Cameylia Salsabila (Welfare : Jurnal Pengabdian Masyarakat, 2024)
Community service between IAIN Kediri and UNISSA Brunei Darussalam through online activities via Zoom aims to promote community economic empowerment through sharia economic principles. The service method involves students identifying community needs, planning joint projects, and implementing online service activities. Through sharia economic projects, including skills training and sharia financial counseling, the aim of this service is to increase the welfare and income of local communities. The results of the service include community economic empowerment, changes in the economic paradigm, and intensive knowledge exchange between students and academics. This collaboration produced a real positive impact, enriching global understanding of sharia economics and making a significant contribution to sustainable development and community empowerment in both countries.